Recommendations for the selection of techniques and components used in congenital heart surgery in Turkey - (:unkn) unknown (BAYCINAR MEDICAL PUBL-BAYCINAR TIBBI YAYINCILIK, 2022)
There is no standard for the selection of technical and mechanical components (heart-lung machine system, oxygenator, arterial and venous cannulae, arterial filter and other specifically-designed components and devices) used in cardiopulmonary bypass in Turkey. The cost of the component plays a significant role in the selection, as well as the preference of the facility. Only a limited number of hospitals decide which components to be used based on scientific data. Studies have confirmed that selected novel techniques and components having no basis of scientific justification may pose risk for the life of the patient in the short- and long-term. The objectives of this study are to show how to use quality-control procedures and scientific data for the selection of novel techniques and components and to share, also, recent techniques experienced to minimize the complication risk after surgery.
Keywords: Cardiopulmonary bypass; component selection; pediatric heart surgery; Turkey; SURGICAL SAFETY CHECKLIST; CEREBRAL OXYGEN-SATURATION; PEDIATRIC CARDIAC-SURGERY; CARDIOPULMONARY BYPASS; ARTERIAL FILTER; BLOOD-FLOW; PERFUSION; PULSATILE; PERFORMANCE; PROTECTION